Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Cafe Brotherhood: Studi Kasus Pada Pelanggan Cafe Brotherhood - Sinaga, Eka Mayastika; Tampubolon, Lasmaria; Sinaga, Shania (Management And Business Progress, 2023)
This study aims to determine the Analysis of Factors Affecting Consumer Satisfaction Cafe Brotherhood. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to 88 respondents to Cafe Brotherhood visitors. The analytical method used in this study uses an instrument test, namely the validity test and reliability test. Classical assumption test, namely normality test, multicollinearity, and heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely t-test (partial). The results show that the price variable (X1) has a significant effect on consumer satisfaction (Y), the product quality variable (X2) has a significant effect on consumer satisfaction (Y), the service quality variable (X3) has a significant effect on customer satisfaction (Y) and the dominant factor influencing it is the variable of product quality on consumer satisfaction.